111 Predictors of Complications After Clipping of Unruptured Intracranial Aneurysms: A National Surgical Quality Improvement Program Analysis. (1st August 2016) - Dasenbrock, Hormuzdiyar H.; Rudy, Robert F.; Gormley, William B.; Smith, Timothy R.; Frerichs, Kai U.; Aziz-Sultan, Mohammad Ali; Du, Rose
Abstract: INTRODUCTION: While obliteration of unruptured aneurysms reduces the risk of subarachnoid hemorrhage, perioperative complications impact the risk-benefit ratio of aneurysm repair, and additional data are needed to optimally risk-stratify patients preoperatively. METHODS: Patients who underwent craniotomy for microsurgical clipping of an unruptured aneurysm were extracted from the prospective National Surgical Quality Improvement Program (NSQIP) registry (2007-2014). Multivariable logistic regression evaluated predictors of developing a complication within 30 days; predictors screened included patient demographics, comorbidities, American Society of Anesthesiologists classification, functional status, and preoperative laboratory values. Independent predictors were utilized to build a predictive scale, which was validated using the Nationwide Inpatient Sample (2002-2011). RESULTS: A total of 626 patients were included in the study population, in whom 19.4% (n = 119) developed any complication and 13.7% (n = 84) a major complication. The NSQIP-unruptured aneurysm scale was constructed based on independent predictors of adverse events: two points were assigned for age 51 to 60 years, cardiac disease, diabetes mellitus, morbid obesity, anemia (hematocrit <36%), operative time 240 to 330 minutes; three points for leukocytosis (white blood cell count >12 000/µL) and operative time greater than 330 minutes; and four points for age greater than 60 years. Increased score was associated with higher odds of a major complication in the study (odds ratio [OR], 1.42; 95% confidence interval [CI], 1.28-1.57, P < .001, C: 0.74) and the validation (OR, 1.21; 95% CI, 1.17-1.25, P < .001, C: 0.62) populations. Greater score was also associated with increased odds of mortality, any complication, stroke or coma, cardiac complications, postoperative mechanical ventilation, venous thromboembolism, infectious complications, reoperation, extended length of stay, and nonroutine hospital discharge in both the study and the validation populations ( P = .04). CONCLUSION: The NSQIP unruptured cerebral aneurysm scale is predictive of several different complications and outcomes after clipping of unruptured aneurysms, and identifies patients with the greatest odds of an adverse event.